2013
DOI: 10.2147/ndt.s46689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rs1080985 single nucleotide polymorphism of the CYP2D6 gene on response to treatment with donepezil in patients with Alzheimer’s disease

Abstract: BackgroundRecent data indicate that the rs1080985 single nucleotide polymorphism of the cytochrome P450 (CYP) 2D6 gene may affect the response to treatment with donepezil in patients with Alzheimer’s disease. There is also evidence that the common apolipoprotein E (APOE) polymorphism may affect the response to treatment with donepezil in Alzheimer’s disease. We investigated the association between response to donepezil and the rs1080985 single nucleotide polymorphism, the minor allele (G) of which was previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…In this study, no difference was observed in the clinical response, regardless of the presence of APOE4 (Table 5). Our findings are different from those obtained by other investigators [30,31], but are in line with the results reported by Rigaud et al [29], Klimkowicz-Mrowiec et al [32], and Lu et al [33]. Lu and colleagues [33] also analyzed the influence of the 3 allele in clinical response and found an increase in the rate of good responders among non-carriers of 3 taking donepezil, a result that was not reproduced in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, no difference was observed in the clinical response, regardless of the presence of APOE4 (Table 5). Our findings are different from those obtained by other investigators [30,31], but are in line with the results reported by Rigaud et al [29], Klimkowicz-Mrowiec et al [32], and Lu et al [33]. Lu and colleagues [33] also analyzed the influence of the 3 allele in clinical response and found an increase in the rate of good responders among non-carriers of 3 taking donepezil, a result that was not reproduced in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…However, the effect was found to be small to moderate. Similar to a study in Polish individuals [ 12 ], findings did not show a significant role of the minor allele in improving the clinical response to donepezil. These contrasting findings suggest that there are additional factors, probably genetic factors that are correlated with ethnicity which are involved in the response to donepezil treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Three studies that have analyzed the interaction between APOE status and rs1080985 did not find a direct interaction between APOE and CYP2D6 polymorphisms [ 11 , 12 , 13 ]. In one of these studies, a marginal significance (p = 0.05) for frequency of the APOE- Ɛ4 and rs1080985 G allele was found, but an independent effect of APOE -Ɛ4 on response to donepezil was not found [ 12 ]. In our study, APOE -Ɛ4 was not significantly associated with the therapeutic response to donepezil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies show evidence of better responses in poor metabolisers although one study found a trend in the opposite direction [29] and no association was found in another study [15].…”
Section: Alzheimer's Diseasementioning
confidence: 97%